2014
DOI: 10.1155/2014/841907
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Adenocarcinoma Occurring 5 Years after Resection of a Primary Pancreatic Adenocarcinoma: A Relevant Differential Diagnosis

Abstract: Ductal adenocarcinoma of the pancreas is a lethal disease. Surgical extirpation only offers the slim chance for long-term survival in localized disease. We report on a 73 year old female patient who initially underwent successful resection of pancreatic adenocarcinoma in May 2005. She was treated with adjuvant chemotherapy with gemcitabine. In October 2010 the patient noticed increasing dyspnea with haemoptysis. She was soon referred to our center. After the diagnosis of pulmonary adenocarcinoma with widesprea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
2
3
0
Order By: Relevance
“…Thus, the post relapse survival after surgery for isolated pulmonary metastases has to be considered with certain precautions. However, it is a well-established observation that a superior DFS is mostly found in patients with pulmonary metastases (19,(31)(32)(33). This is in-line with a recent SEER analysis from Liu et al, who demonstrated that resection in highly selected patients with either isolated synchronous or metachronous pulmonary metastases is correlated with a signi cant survival bene t in PDAC (34).…”
Section: Discussionsupporting
confidence: 70%
“…Thus, the post relapse survival after surgery for isolated pulmonary metastases has to be considered with certain precautions. However, it is a well-established observation that a superior DFS is mostly found in patients with pulmonary metastases (19,(31)(32)(33). This is in-line with a recent SEER analysis from Liu et al, who demonstrated that resection in highly selected patients with either isolated synchronous or metachronous pulmonary metastases is correlated with a signi cant survival bene t in PDAC (34).…”
Section: Discussionsupporting
confidence: 70%
“…Thus, the relapse speci c survival after surgery for isolated pulmonary metastases has to be considered with certain precautions. However, it is a well established observation that a superior survival until relapse diagnosis is mostly found in patients with pulmonary metastases [19,[31][32][33]. This is in-line with a recent SEER analysis from Liu et al who demonstrated that resection in highly selected patients with either isolated synchronous or metachronous pulmonary metastases is correlated with a signi cant survival bene t [34].…”
Section: Discussionsupporting
confidence: 61%
“…A metachronous tumor is defined as the development of two primary malignant lesions usually with lag time, often years, between the first and second lesion [ 3 ]. Although rare, there have been many reports of metachronous pancreatic and lung adenocarcinoma [ 4 – 6 ]. Metachronous malignant lesions pose diagnostic dilemma since they are hard to differentiate from other metastatic lesions [ 4 – 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although rare, there have been many reports of metachronous pancreatic and lung adenocarcinoma [ 4 – 6 ]. Metachronous malignant lesions pose diagnostic dilemma since they are hard to differentiate from other metastatic lesions [ 4 – 6 ].…”
Section: Introductionmentioning
confidence: 99%